Data center virtualization and visualization - Xu, Weida (2016)
The emergence of cloud computing has promoted growing demand and rapid deployment of data centers. However, data center operations require a set of sophisticated skills (e.g., command-line-interface), resulting in a high operational cost. In this research, to reduce the data center operational cost, we design and build a novel cloud data center management system, by leveraging the concept of 3D gamification. To this end, we implement two types of functions, including multi-source data monitoring and data center visualization. For data collecting, we build a suit of unified middleware to monitor and control the three intrinsic subsystems in a data centre, including ICT, power and cooling. Our system consists of three main parts, i.e., datasource adapters for information collection over various subsystems in data center, a unified message bus for data transferring, and a high-performance database for persistent data storage. For data visualization, we apply data visualization techniques to overlay operational status upon a data center 3D model, allowing the operators to monitor the real-time situation and control the data center from a friendly user interface. We have successfully implement a light–weight mobile application, together with a cloud-based service engine. Heavy-life computation tasks (e.g., visual rendering, CFD emulation, etc) are offloaded from the mobile application to the cloud engine. enabling mobility and ubiquity in data center operations. Our application, owing to its intuitive user interface and visualization capability, renders its potential wide adoption for a variety of user cases, ranging from data center operations, marketing campaigns, staff training, and business decision. It potentially creates new revenue streams for IT department.